PERMASALAHAN BULLWHIP EFFECT PADA SUPPLY CHAIN - Tita Talitha (TECHNO SCIENCE, 2010)
In supply chain management, bullwhip effect phenomenon has attracted attention. Bullwhipeffect shows how small changes at the end of the supply chain demand strengthened for further chainoperations. That demand forecast variance contributes influential in the chain. With thisunderstanding, the author experimented with the case of a stable demand with single 5% change indemand. Results shown in tables and graphs. Increased variability of production orders and stocksupply chain is clear. Stock shows a lack of synchronization between supply chain members ascorrupt key information about the actual demand. When we understand the nature of supply chaindynamics.